Job-Related Attitudes and the Correlation to Attitude Toward Technology in Higher Education Faculty - Hardy, Dorea Michelle (My University, 2019)
A significant majority of research focusing on both technology and burnout has focused on how new technology affects the job-related attitudes of the employees. This research looked at technology and burnout from a different perspective. The technology in question had been in place for several years. Most University System of Georgia (USG) faculty should have already been exposed to the D2L Brightspace platform. However, around the time of this research (2018), the technology was receiving an upgrade, moving to the version called “Daylight.” The aim of this study was twofold. First, this study intended to add to the limited knowledge base of technology acceptance in the context of an upgrade. Second, this study investigated a snapshot of job-related attitudes of the employees. The Maslach Burnout Inventory–Educators Survey (MBI-ES) was joined with the Technology Acceptance Model (TAM) to see how the job-related attitudes of the employees affected their acceptance of the technology upgrade to the Learning Management System (LMS).
Chapter I: INTRODUCTION 1 -- Statement of the Problem 4 -- Purpose of the Study 5 -- Research Questions 6 -- Research Methodology 6 -- Significance of the Study 7 -- Conceptual Frameworks 8 -- Limitations of the Study 10 -- Definition of Terms 11 -- Course Categorizations 13 -- Organization of the Study 14 -- Chapter II: LITERATURE REVIEW 16 -- Methods 17 -- Technology Acceptance Model 18 -- Utilization of TAM outside of Higher Education 22 -- Utilization of TAM in Higher Education 32 -- Burnout 37 -- Stress and Technology 39 -- Stress and Faculty 41 -- Conservation of Resources 43 -- Maslach Burnout Inventory 45 -- Summary 50 -- Chapter III: METHODOLOGY 52 -- Research Design 52 -- Independent Variables 54 -- Dependent Variables 56 -- Participants 56 -- Target Population 56 -- Accessible Population 57 -- Sampling Procedure 57 -- Anticipated Sample 58 -- Potential Risks and Ethical Considerations 60 -- Instrumentation 60 -- Technology Acceptance Model 62 -- Validity of TAM 62 -- Reliability of TAM 63 -- Maslach Burnout Inventory 63 -- Validity of MBI-ES 64 -- Reliability of MBI-ES 66 -- Data Collection 66 -- Data Management 68 -- Data Analysis Plan 69 -- Pre-Analysis Data Screen 69 -- Reliability 70 -- Research Questions 70 -- Research Question One 70 -- Research Question Two 70 -- Research Question Three 71 -- Sample Size Justification 73 -- Summary 74 -- Chapter IV: RESULTS 76 -- Pre-Analysis Data Screen 76 -- Demographics of Sample 76 -- Descriptive Statistics of Continuous Variables 78 -- Research Question One 78 -- Research Question Two 83 -- Research Question Three 86 -- Summary 91 -- Chapter V: DISCUSSION 92 -- Interpretation of the Findings 93 -- Implications for Theory and Practice 94 -- Limitations 97 -- Recommendations for Future Research 99 -- Conclusion 101 -- REFERENCES 103
Keywords: Dissertations, Academic--United States; Burn out (Psychology); Technology.; Education, Higher; Employees--Attitudes